Modelling and analysis of leaching of copper from volcanic ash soil : a thesis presented in partial fulfilment of the requirments [i.e. requirements] for the degree of Master of Technology in Environmental Engineering - He, Dali (Massey University, 1999)
Soil contaminated by heavy metal ions has become a global problem. Besides legislation to restrict the input of heavy metals, remediation of contaminated soil is also essential. The most common means of remediation is leaching. There have been many studies published in this field, some of which relate to development of mathematical models. Volcanic ash soil is common in New Zealand. Developing a model to predict the process of leaching heavy metal from volcanic ash soil is important for New Zealand. No model was found for predicting the process of leaching heavy metal from volcanic ash soil. Heavy metal soil contamination can not be remedied by microorganisms, so the heavy metals will inevitably accumulate in soils over time. Once heavy metals have accumulated in soil to exceed a threshold, they will be released and then be taken up by plants, entering the food chain or moving into the groundwater system. Therefore, it is necessary to leach the heavy metals from the contaminated soil. The batch stirred process is a fast and convenient method, and it is easily used in the field. The main purpose of this study is to develop a model that can predict the bulk liquid concentration of heavy metal in the stirred vessel. In the present study, the internal model is pore diffusion model. The explicit method is used to translate a partial differential equation to a finite difference equation. The results from thermodynamic and kinetic experiments agree with the model. With the exception of the equilibrium parameters for Freundlich isotherm derived by experiment, all other parameters were obtained from literature on volcanic ash soil. Therefore, the model can be used for leaching of other heavy metals from volcanic soil under similar conditions. The leaching of heavy metals from volcanic soil is shown to be an internal diffusion controlled process, so increasing the agitating speed in a stirred reactor is of no use for improving the mass transfer. Decreasing the size of volcanic soil aggregates by breaking them clearly increases the rate of the leaching process. The equilibrium relationships of the adsorption process and the desorption process are different for the system, and there is a hysteresis.
Keywords: Volcanic ash, tuff, etc.; Leaching; Mathematical models; Copper content; Soils